Hubungan Antara Kecerdasan Emosional Dan Depresi Pada Ibu Yang Memiliki Anak Dengan Gangguan Autisme - Meliani Meliani; Jenny Lukito Setiawan; Monique Elizabeth Sukamto (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2007)
Mothers usually expect their children to grow well and healthy. Therefore, having an autistic child is a very difficult experience as this may make mothers feel frustrated and sad. Continuous negative feelings could make the mothers feel depressed. This study aims to examine the correlation between emotional intelligence and depression on mothers with an autistic child. Twenty-six mothers (27) with an autistic child below 12 years old participated in the study by filling in the questionnaires of emotional intelligence and depression. Date were then analyzed statistically by using the Product Moment Correlation Test. Findings showed that there was a significant negative correlation between emotional intelligence and depression (r=-0.571, p < 0.05) The findings suggest that the higher the emotional intelligence a mother has, the lower the depression level she experiences. Findings also show the indication of association between work status and depression on mothers with an autistic child. The implications of the findings are explored further. Key words            :    autism, emotional intelligence, depression